Toxic Effect Of The Compound 1,3 Bis (P-Hydroxyphenyl) Urea On Triiodothyronine (T3) Hormone Levels In Pregnant White Rats (Rattus Norvegicus L.) - Putri Aisyia Fauzi, Ziza; Harahap, Urip; Yuandani, Yuandani; Berkat Waruwu, Syukur; Purnomo, Hari; Satria, Denny (Publisher Cv. Inara, 2023)
Non-steroidal anti-inflammatory drugs (NSAIDs) are among the most commonly prescribed drugs for pregnant women to treat fever, pain and inflammation. Specific NSAIDs can displace thyroid hormone from its protein binding sites, causing thyroid hormone measurement problems. 1,3 bis (p-Hydroxyphenyl)urea is a modified p-aminophenol compound with potent analgesic and anti-inflammatory activity and less toxicity. This study is a follow-up to previous research to observe the toxic effect on triiodothyronine hormone levels after administration of 1,3 bis(p-Hydroxyphenyl)urea compound in pregnant white rats. The toxic effect test was carried out by giving the test preparation to pregnant rats, which had been divided into five groups, namely the normal control group (CMC-Na 0.5%), the positive control (Gabapentin 50 mg/kg BW), Compound 1.3 bis (p- Hydroxyphenyl)urea at a dose of 50 mg/kg BW, 500 mg/kg BW and 1000 mg/kg BW. Mice were given the test preparation every day from the 6th to the 15th day of pregnancy. Blood was taken on the 16th day, and T3 hormone levels were measured using the ELISA method. The results showed that the T3 hormone levels in the 1,3 bis(p-Hydroxyphenyl)urea group had no significant difference from the normal control group, so it was concluded that 1,3 bis(p-Hydroxyphenyl)urea) did not have a significant effect on the hormone T3.",